Analysis of the Physicochemical Properties of Lanolin-Based Lipstick from Sheep Wool with Addition of Dragon Fruit Exocarp Extract (Hylocereus polyrhizus) - April Mesrianti Sukatendel; Nurzainah Ginting; Rita Rosmala Dewi (Talenta Publisher, 2025)
Lanolin (Adeps lanae), derived from sheep wool, is a complex lipid composed of fatty esters such as cholesterol, cetyl alcohol, and carnuba alcohol. It acts as an effective natural humectant that maintains moisture and enhances the stability of cosmetic formulations, including lipstick. This study aimed to study a lanolin-based lipstick incorporating dragon fruit (Hylocereus polyrhizus) exocarp extract as a natural colorant and antioxidant. The dragon fruit exocarp extract and lanolin were obtained using previously validated methods assisted by rotary evaporation. A completely randomized design (RAL) was implemented with four treatments: P0 (0%), P1 (20%), P2 (40%), and P3 (60%) exocarp extract concentrations in the lipstick formulation. Evaluated parameters included melting point, pH, spreadability, and homogeneity. Data were analyzed via ANOVA followed by Tukey’s test at a 5% significance level. Results indicated that treatments had a significant effect (P < 0.05) on all evaluated properties. The highest melting point was observed in P0 (66.60 °C) and the lowest in P3 (60.60 °C), both within the SNI 16 4769 1998 standard range (50–70 °C). The highest pH was recorded in P0 (5.16 ± 0.07), while the lowest was in P3 (4.41 ± 0.02), nearing the physiological pH of the lips (3.8–4.7). The P1 formulation (20%) exhibited the best homogeneity and spreadability.